Getting Real About Killing and Allowing to Die: A Critical Discussion of the Literature - Stumpf, Andrew; Rogalski, Dominic (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
The moral significance of the distinction between killing and allowing to die has played a key role in debates about euthanasia and physician assisted suicide. Since the withdrawal of life-sustaining treatment is held as morally permissible in the medical community, it follows that if there is no morally significant difference between killing and allowing to die, then there is no morally significant difference between withdrawing life-sustaining treatment or administering a lethal injection to end a patient’s life. Consistency then requires that voluntary active euthanasia (VAE) is also morally permissible. The debates over whether the distinction is morally significant have carried on for decades with little hope of consensus. We begin by surveying the literature to identify common argumentative strategies used in defending or rejecting the distinction’s significance. We observe, based on our review, that many of these strategies operate in ways that are conceptually removed from the concrete clinical situation of physicians involved in practices that lead to patient death (by withdrawal of treatment or VAE). We conclude by arguing for a novel way of moving the debate forward indicated by our reading of the literature, namely, by paying careful attention to the moral experience of physicians involved in end-of-life interventions to understand how they experience these practices. Exploring physician experience can reveal how the distinction may or may not be useful for moral deliberation and can provide the needed context to theorize about the distinction in a more empirically informed and practically useful way.